Pengaruh Pembelajaran Kewirausahaan dan Motivasi Berwirausaha Terhadap Minat Berwirausaha Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Bandar Lampung - Al Affan, Dhalvi; Harpain (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Indonesia is currently facing a demographic bonus with the majority of its population being of productive age, which provides a great opportunity to increase economic productivity through entrepreneurship. Bandar Lampung University supports this through various entrepreneurship programs, such as the Innovation and Ideavation Academy. The study aims to examine the impact. The study explores the impact of entrepreneurial education and motivational factors on students' entrepreneurial interest at the Faculty of Economics and Business, Bandar Lampung University. A quantitative approach was employed, collecting data from a purposive random sample of 73 students from the 2021 cohort via an online questionnaire. The data analysis, conducted with SPSS, included normality testing, linear regression, as well as F and T tests. The results reveal that both entrepreneurial education and motivation significantly influence the entrepreneurial interests of these students., in choosing entrepreneurship. both separately and together, explained 66.2% of the variation in entrepreneurial interest. These findings highlight the importance of these two factors in encouraging students' interest in entrepreneurship. This research proves that entrepreneurial learning and motivational encouragement play a crucial role in boosting students' interest in launching their own business.